2016
DOI: 10.1002/cam4.895
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial pathway and endoplasmic reticulum stress participate in the photosensitizing effectiveness of AEPDT in MG63 cells

Abstract: Photodynamic therapy (PDT) is a promising treatment in cancer therapy, with a photosensitizer activated by visible light. Aloe‐emodin (AE) is a promising photosensitive agent. In this study, the photosensitizing effects and possible mechanisms of AE‐PDT in MG63 cells were evaluated. The efficiency of AE‐PDT was analyzed by MTT assay. The mode of cell death was investigated by Hoechst 33,342 staining and flow cytometer. The intracellular distribution of AE was detected with confocal microscopy. The formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Because the subcellular localization of a photosensitizer can impact its mechanisms of action, we considered that the mitochondria-caspase pathway was probably involved in the apoptotic mechanism. It is well known that Bax and cleaved Caspase-3 (active Caspase-3) are pro-apoptotic proteins and Bcl-2 is an antiapoptotic protein[20-23]. As expected, Bax and cleaved Caspase-3 expression was significantly upregulated by YLG-1-PDT, while Bcl-2 expression exhibited the opposite results.…”
Section: Discussionsupporting
confidence: 69%
“…Because the subcellular localization of a photosensitizer can impact its mechanisms of action, we considered that the mitochondria-caspase pathway was probably involved in the apoptotic mechanism. It is well known that Bax and cleaved Caspase-3 (active Caspase-3) are pro-apoptotic proteins and Bcl-2 is an antiapoptotic protein[20-23]. As expected, Bax and cleaved Caspase-3 expression was significantly upregulated by YLG-1-PDT, while Bcl-2 expression exhibited the opposite results.…”
Section: Discussionsupporting
confidence: 69%
“…In this view, the use of photodynamic therapy (PDT) as a co-adjuvant therapy for cancer treatment is increasingly being considered [ 26 , 27 ]. PDT has been successfully used to kill OS cells in vitro [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ] and in vivo [ 35 , 36 , 37 ]. In a previous study, we successfully demonstrated the in vitro efficacy of PDT in OS cell lines by using porphyrin-loaded poly-methyl methacrylate nanoparticles [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several preclinical in vitro and in vivo studies in OS showed that PDT is able to induce apoptosis (activation of mitochondrial and/or caspase pathways, and/or ROS increase), autophagy (activation of ROS-Jnk signaling pathway) and/or to arrest cells at the G2/M phase, depending on PS employed (Table 4) [136,137,138,139,140,141,142,143,144,145,146,147,148]. In addition, PDT can be employed in combination with other biophysical stimuli: low-level light therapy (LLLT) combined with N-aspartyl chlorin e6-PDT (NPe6-PDT) to enhance the cytotoxicity in MG-63 cells by increasing ROS and ATP [149].…”
Section: Application Of Biophysical Therapies In Osteosarcomamentioning
confidence: 99%